Ubiquitin-Dependent Modification of Skeletal Muscle by the Parasitic Nematode, Trichinella spiralis. - Rhiannon R White; Amy H Ponsford; Michael P Weekes; Rachel B Rodrigues; David B Ascher; Marco Mol; Murray E Selkirk; Steven P Gygi; Christopher M Sanderson; Katerina Artavanis-Tsakonas (PLoS Pathogens, 2016)
Trichinella spiralis is a muscle-specific parasitic worm that is uniquely intracellular. T. spiralis reprograms terminally differentiated skeletal muscle cells causing them to de-differentiate and re-enter the cell cycle, a process that cannot occur naturally in mammalian skeletal muscle cells, but one that holds great therapeutic potential. Although the host ubiquitin pathway is a common target for viruses and bacteria during infection, its role in parasite pathogenesis has been largely overlooked. Here we demonstrate that the secreted proteins of T. spiralis contain E2 Ub-conjugating and E3 Ub-ligase activity. The E2 activity is attributed to TsUBE2L3, a novel and conserved T. spiralis enzyme located in the secretory organ of the parasite during the muscle stages of infection. TsUBE2L3 cannot function with any T.spiralis secreted E3, but specifically binds to a panel of human RING E3 ligases, including the RBR E3 ARIH2 with which it interacts with a higher affinity than the mammalian ortholog UbcH7/UBE2L3. Expression of TsUBE2L3 in skeletal muscle cells causes a global downregulation in protein ubiquitination, most predominantly affecting motor, sarcomeric and extracellular matrix proteins, thus mediating their stabilization with regards to proteasomal degradation. This effect is not observed in the presence of the mammalian ortholog, suggesting functional divergence in the evolution of the parasite protein. These findings demonstrate the first example of host-parasite interactions via a parasite-derived Ub conjugating enzyme; an E2 that demonstrates a novel muscle protein stabilization function.